Fiber optic hydrogen sensor based on a Fabry–Perot interferometer with a fiber Bragg grating and a nanofilm. Issue 9 (23rd March 2021) - Luo, Junxian; Liu, Shen; Chen, Peijing; Lu, Shengzhen; Zhang, Qiang; Chen, Yanping; Du, Bin; Tang, Jian; He, Jun; Liao, Changrui; Wang, Yiping
Abstract : A novel probe-type FPI-based fiber optic hydrogen sensor with a graphene–Au–Pd sandwich structure film and FBG is proposed and experimentally demonstrated in this study. Abstract : Hydrogen is widely used in industrial production and clinical medicine, and as fuel. Hydrogen becomes explosive when the hydrogen–air mixture ranges from 4 to 76 vol%; thus, a rapid hydrogen concentration measurement is particularly important in practical applications. We present a novel fiber optic hydrogen sensor with fast response fabricated from a graphene–Au–Pd sandwich nanofilm and an ultrashort fiber Bragg grating. The response time is only 4.3 s at a 3.5 vol% hydrogen concentration. When the measured hydrogen concentration was increased from 0 to 4.5 vol%, the optical resonance dip in the sensor near 1550 nm shifted by 290 pm. In addition, the sensor has an insertion loss of only −2.22 dB, a spectral contrast of 10.8 dB, and a spectral finesse of 5. Such a flexible, fast-response sensor is expected to be used in the development of hydrogen sensors with low power consumption.